Effect of interfacial oxide thickness on the photocatalytic activity of magnetron‐sputtered TiO2 coatings on aluminum substrate. Issue 12 (14th August 2015) - Davíðsdóttir, Svava; Petit, Jean‐Pierre; Shabadi, Rajashekhara; Canulescu, Stela; Almtoft, Klaus P.; Dirscherl, Kai; Andersen, Inge H.; Ambat, Rajan
Abstract : The influence of the coating/substrate interface on the photocatalytic behavior of Al–TiO2 coatings was investigated. The TiO2 coatings were prepared by magnetron sputtering. The nanoscale structure of the coating was analyzed using X‐ray diffraction; atomic force microscopy; scanning electron microscopy; and transmission electron microscopy. The photocatalytic behavior was investigated through optical spectrophotometry studies and electrochemical experiments; as photo voltage; photocurrent; and electrochemical impedance measurements. Consistent results from both optical and electrochemical measurements showed a maximum UV‐light absorption by titanium dioxide occurring slightly prior to the energy of the maximum photocurrent. The photocurrent of titanium dioxide decreases with increasing thickness of the aluminum oxide interface layer. Aluminum oxide acts as an insulator; disfavoring the electron transport between the coating and the metallic substrate. The highest photocurrents were indeed obtained when the thickness of interfacial aluminum oxide could be reduced by sputtering a thin Ti layer prior to TiO2 coating. Photocurrent plotted for different photon energy for a TiO2 coating on a Ti interlayer consisting of both rutile and anatase. Two photon‐excitation peaks from the TiO2 coating (anatase and rutile) are observed at a potential of 0.34 V versus SHE, while only one peak was observed at a potential 0.14 V versus SHE closer to the conduction band.